Care for older adults with dementia: PACE day care or residential dementia care units?. (March 2021) - Chen, Liang-Yu; Hsu, Ting-Jung; Ke, Li-Ju; Tsai, Hui-Te; Lee, Wen-Ting; Peng, Li-Ning; Lin, Ming-Hsien; Chen, Liang-Kung
Highlights: Persons with dementia (PwD) are at greater risk of premature mortality, disability, and institutionalization. Hence, a holistic care model is recommended to maintain their independent livings in the communities. Compraing with institutional care model, the Program of All-inclusive Care for the Elderly (PACE) model provides a comprehensive care assistance to meet the complex needs of PwD in the communities. Our study revealed the benefitial role of PACE model on reducing hospital admission, maintaining physical independency, improving cognitive performance, and decreasing depressive mood among community-dwelling PwD. Abstract: Background: Persons with dementia (PwD) are at greater risk for various adverse health outcomes, and the best care model remains to be determined. This study aimed to compare the physical and neurocognitive performance of PwD in the Program of All-inclusive Care for the Elderly (PACE) and residential dementia care units. Methods: This was a case-control study comparing outcomes between care recipients of PACE services (PC group) and residential dementia care (RC group). Demographic characteristics, underlying diseases, physical function, cognitive function, mood status, and behavioral and psychotic symptoms of dementia (BPSDs) were assessed every 3-6 months in both groups, while frailty status and Timed Up-and-Go Test (TUGT) performance were assessed every 6 months in the PC group only. Results: Overall, 96 participants (PC group: 25, RC group: 71; mean age: 86.4 ± 6.8 years) were enrolled with the median follow-up period of 43.6 weeks. Lower incidence of hospital admissions was noted in the PC group (0.52 ± 1.12 vs 1.38 ± 2.49 admissions/1, 000 person-days, p=0.023), even though the PC group had higher multimorbidity and more severe BPSDs. During the study period, the PC group showed a significant improvement in body mass index, less physical dependence, better cognitive performance and reduced depressive mood. In addition, the PC group showed improvement in frailty, leisure hour activities, and TUGT results. However, participants in the PC group were more likely to experience BPSD deterioration (β coeff.: 0.193, 95% CI: 0.121- 0.265). Conclusion: The PACE services significantly reduced unexpected hospital admissions of PwD, facilitated the maintenance of physical independence, and improved cognitive performance and mood status. Further randomized controlled studies are needed to determine the most appropriate care model for PwD.